Public Health Research Ethics and Clinical Research Ethics. How we differentiate? (Bangladesh Journal of Bioethics, 2018)
This article talks about both clinical research ethics and public health research ethics. Clinical research ethics are defined as set of relevant ethics considered necessary for the conduct of clinical trials in field of the clinical research. While public health research ethics is mainly aimed at finding out what is best for the communities and the populations rather than the individuals. Research ethics is mainly focused on the protection of individual participants and some of the research norms and accepted principles may be challenging when applying in some of the research contexts.